Case report: SAF-189s is a potent inhibitor in a lorlatinib-resistant NSCLC patient with acquired compound mutations ALK L1196M and D1203N - Li, Na; Li, Huihui; Wang, Ding; Xu, Xiaoling (Frontiers in Pharmacology, 2023)
Acquired anaplastic lymphoma kinase (ALK) mutation is the major resistant mechanism to ALK tyrosine kinase inhibitors (TKIs) in non-small cell lung cancer (NSCLC) patients. At present, treatment options after acquiring secondary ALK mutations are still limited. Here, we report on a patient with metastatic ALK-rearranged NSCLC who was sequentially treated with ALK TKIs, from crizotinib to lorlatinib, and developed rare acquired compound ALK mutations (L1196M and D1203N) that confer resistance to lorlatinib. Moreover, our report describes the clinical response of an NSCLC patient with these compound mutations to multiple anti-tumor therapies. Among them, the patient was treated with SAF-189s 120 mg daily and had a stable disease lasting 3 months. Chemotherapy (pemetrexed-carboplatin) combined with bevacizumab was then administered. She achieved a partial response, which was maintained for 7 months as the best response. Since both SAF-189s and chemotherapy have shown a clear antitumor effect, they may be viable therapeutic options for these patients. Thus, our study can provide some reference in the treatment of NSCLC patients with ALK L1196M/D1203N compound mutations.